2019
DOI: 10.1155/2019/2350694
|View full text |Cite
|
Sign up to set email alerts
|

A Double Adaptive Approach to Tackle Malicious Users in Cognitive Radio Networks

Abstract: Cognitive radio (CR) is being considered as a vital technology to provide solution to spectrum scarcity in next generation network, by efficiently utilizing the vacant spectrum of the licensed users. Cooperative spectrum sensing in cognitive radio network has a promising performance compared to the individual sensing. However, the existence of the malicious users’ attack highly degrades the performance of the cognitive radio networks by sending falsified data also known as spectrum sensing data falsification (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 9 publications
0
34
0
Order By: Relevance
“…In the figure, an FC receives sensing statistics of the PU channel from M users including both normal SUs and MUs. According to the operating criteria of MUs, an AY MU reports higher energy statistics to the FC irrespective of the actual status of the PU channel as if the PU channel is always busy [29]. us, if there exist AY MUs in CSS, the data rate of the secondary system can be severely reduced.…”
Section: Proposed Cooperative Spectrum Sensingmentioning
confidence: 99%
See 1 more Smart Citation
“…In the figure, an FC receives sensing statistics of the PU channel from M users including both normal SUs and MUs. According to the operating criteria of MUs, an AY MU reports higher energy statistics to the FC irrespective of the actual status of the PU channel as if the PU channel is always busy [29]. us, if there exist AY MUs in CSS, the data rate of the secondary system can be severely reduced.…”
Section: Proposed Cooperative Spectrum Sensingmentioning
confidence: 99%
“…Various attacks which severely degrade the performance of the CSS have been studied in the CRN. e representative attacks are Byzantine users' attack, jamming attack, and primary user emulation attack (PUEA) [29][30][31][32][33]. e Byzantine users' attack is a type of spectrum sensing data falsification (SSDF) attack, where malicious users (MUs) report false information to the FC.…”
mentioning
confidence: 99%
“…Feng et al reported the collusive SSDF attack method and proposed a two-level (the request-level and feedback-level) and XDA defence scheme from the perspective of XOR distance analysis to defend against this attack in [24,25], respectively. Khan et al in [26] proposed a double adaptive thresholding technique in order to differentiate legitimate users from doubtful and malicious users. Yuan et al in [27] proposed a maximum mean discrepancy (MMD)-based secure fusion strategy to defend against intelligent SSDF attack for collaborative spectrum sensing in CRNs.…”
Section: Related Workmentioning
confidence: 99%
“…A multinomial Bayesian trust model is proposed in Bhattacharjee et al (2015) to defend against SSDF attacks by classifying nodes into honest or malicious. A double adaptive threshold technique is proposed in Khan et al (2019) to differentiate the honest and malicious nodes by assigning weights to nodes using a Maximal Ratio Combining (MRC) scheme. Dempster-Shafer evidence theory is used at the FC to combine the decision of all the honest nodes.…”
Section: Introductionmentioning
confidence: 99%